因式分解m²n-5mn+6n a²-b²-2a+1
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 09:53:34
因式分解m²n-5mn+6na²-b²-2a+1因式分解m²n-5mn+6na²-b²-2a+1因式分解m²n-5mn+6na
因式分解m²n-5mn+6n a²-b²-2a+1
因式分解m²n-5mn+6n a²-b²-2a+1
因式分解m²n-5mn+6n a²-b²-2a+1
m²n-5mn+6n
=n(m²-5m+6)
=n(m-2)(m-3)
a²-b²-2a+1
=(a²-2a+1)-b²
=(a-1)²-b²
=[(a-1)+b][(a-1)-b]
=(a+b-1)(a-b-1)
明白请采纳,
有新问题请求助,
原式=n(m²-5m+6)
=n(m-2)(m-3)
原式=(a²-2a+1)-b²
=(a-1)²-b²
=(a+b-1)(a-b-1)
m²n-5mn+6n
=n(m²-5m+6)
=n(m-3)(m-2)
a²-b²-2a+1
= a²-2a+1-b²
=(a-1)²-b²
=(a-1+b)(a-1-b)
m²n-5mn+6n
=n(m²-5m+6)
=n(m-2)(m-3)
a²-b²-2a+1
=(a²-2a+1)-b²
=(a-1)²-b²
=(a-1+b)(a-1-b)